2004
DOI: 10.1167/iovs.04-0072
|View full text |Cite
|
Sign up to set email alerts
|

Krüppel-like Factor 15, a Zinc-Finger Transcriptional Regulator, Represses the Rhodopsin and Interphotoreceptor Retinoid-Binding Protein Promoters

Abstract: The zinc finger containing transcription factor KLF15 is a transcriptional repressor of the rhodopsin and IRBP promoters in vitro and, in the retina, is a possible participant in repression of photoreceptor-specific gene expression in nonphotoreceptor cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(41 citation statements)
references
References 54 publications
2
39
0
Order By: Relevance
“…This mode assumed the form of genes exhibiting greater dex induction in Klf15 Ϫ/Ϫ mouse lungs than WT mouse lungs (Fig. 2C), consistent with a repressive role for KLF15, which has previously been reported to act as either an activator or a repressor (19,33), depending on the promoter context. The GR-induced, KLF15-repressed gene set was strongly enriched for genes implicated in metal binding and targets of N-glycosylation (see Table S4 in the supplemental material), among other overrepresented processes, again suggesting that functional significance is associated with specific patterns of GR-KLF15 dependency.…”
Section: Gr-klf15-dependent Transcriptional Programmingsupporting
confidence: 80%
“…This mode assumed the form of genes exhibiting greater dex induction in Klf15 Ϫ/Ϫ mouse lungs than WT mouse lungs (Fig. 2C), consistent with a repressive role for KLF15, which has previously been reported to act as either an activator or a repressor (19,33), depending on the promoter context. The GR-induced, KLF15-repressed gene set was strongly enriched for genes implicated in metal binding and targets of N-glycosylation (see Table S4 in the supplemental material), among other overrepresented processes, again suggesting that functional significance is associated with specific patterns of GR-KLF15 dependency.…”
Section: Gr-klf15-dependent Transcriptional Programmingsupporting
confidence: 80%
“…Among the set of retrieved TFs ( Figure 1A) KLF8 and -15 belong to the Krüppel-like factor (KLF) gene family (16), which possess a zinc-finger structure (KRAB-ZNF TFs) and recognize the GT-box and the core motif CACCC present in the hRHO-cis (16). In particular, KLF15 has a wide matrix sequence highly overlapping the ZF6-cis sequence (Supplemental Table 1; supplemental material available online with this article; https://doi.org/10.1172/jci.insight.96560DS1) and is expressed throughout the retina but not in photoreceptors (17) and thus can be excluded from having a regulatory function in these cells. In addition, although KLF15 exerts a wide range of regulatory functions in different organs and in system homeostasis (18)(19)(20), the mouse knockout does not exhibit prominent phenotypes (21).…”
Section: Resultsmentioning
confidence: 99%
“…KLF15 Is Activator of D4Z4 Enhancer-Depending on the context, KLF15 can function as an activator (42,43) or a repressor (30,44,45). To better analyze its role, as well as that of SP1 vis à vis the D4Z4 enhancer, we first tested whether ectopically expressed KLF15 and SP1 could activate the D4Z4 enhancer.…”
Section: Resultsmentioning
confidence: 99%
“…KLF15, a member of the Krüppel-like transcription factors, was first identified as a repressor of kidney-specific chloride channel CLC-K1 (50), but in other works it was demonstrated that KLF15 can also act as an activator of transcription (30,47). The expression levels of KLF15 are the highest in kidney, liver, pancreas, and cardiac and skeletal muscle (50).…”
Section: Discussionmentioning
confidence: 99%